2017
DOI: 10.1101/137976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lewy pathology in Parkinson’s disease consists of a crowded organellar, membranous medley

Abstract: SummaryParkinson’s disease, the most common age-related movement disorder, is a progressive neurodegenerative disease with unclear etiology. Key neuropathological hallmarks are Lewy bodies and Lewy neurites, which are neuronal inclusions that are immunopositive for the protein α-synuclein. In-depth ultrastructural analysis of this Lewy pathology is crucial to understanding pathogenesis and progression of the disease. Using correlative light and electron microscopy/tomography on brain tissue from five Parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 75 publications
1
46
0
3
Order By: Relevance
“…Recently, we demonstrated that LBs contain increased protein and lipid levels using a label-free nonlinear optical imaging technique, CARS, on native brain tissue sections in combination with confocal microscopy 32 . Here, we applied the a similar pipeline (Supplementary Figure 11) on sections of fresh-frozen midbrain tissue -including the SNpc -of 5 PD patients ( Supplementary Table 2), to explore the distribution of lipid and protein contents in Ser129-p aSyn-immunopositive inclusions.…”
Section: Lipids and Proteins Are Centralized In Nigral Asyn-positive mentioning
confidence: 99%
“…Recently, we demonstrated that LBs contain increased protein and lipid levels using a label-free nonlinear optical imaging technique, CARS, on native brain tissue sections in combination with confocal microscopy 32 . Here, we applied the a similar pipeline (Supplementary Figure 11) on sections of fresh-frozen midbrain tissue -including the SNpc -of 5 PD patients ( Supplementary Table 2), to explore the distribution of lipid and protein contents in Ser129-p aSyn-immunopositive inclusions.…”
Section: Lipids and Proteins Are Centralized In Nigral Asyn-positive mentioning
confidence: 99%
“…They may also be observed in neurites but rarely in the extracellular space. However, their structure is highly heterogeneous and has been shown to include various organelles (Kuusisto, Parkkinen & Alafuzoff, ; Sharamoradian, Britschgi, Stahlberg, Berg & Lauer, ). The precise biochemical composition of LB remains elusive but α‐syn is a major component, among other insoluble proteins such as ubiquitin (Lowe, Blanchard, Morrell, Lennox & Reynolds, ; Maroteaux et al., ; Spillantini et al., ).…”
Section: Synucleinopathymentioning
confidence: 99%
“…Given that LBs have been consistently shown to have complex composition and organization and usually contain other non-proteinaceous material (lipids) 25,26 and membranous organelles 8,[27][28][29][30][31][32] , we hypothesized that the transition from fibrils to LB might require time and could be driven by post-translational modifications and structural rearrangements of the fibrils. By extending the characterization of this neuronal seeding model from 11-14 days to 21 days, we were eventually able to observe the transition from fibrils to α-syn rich inclusions that recapitulate the biochemical, morphological, and structural features of the bona fide human LBs, including the recruitment of membranous organelles and accumulation of phosphorylated and C-terminally truncated α-syn aggregates [33][34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%